2021
DOI: 10.3390/polym13213793
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Assessment of Polypropylene Production in the Gulf Cooperation Council (GCC) Region

Abstract: The environmental impacts of the polypropylene (PP) manufacturing process are not fully understood in the Gulf Cooperation Council (GCC) region. There is a growing interest in assessing the environmental impacts of this highly demanded product, especially for the petrochemical industry sector. This research examines the environmental impacts of the polypropylene manufacturing process using a life cycle assessment (LCA) approach. Gabi software is selected to carry out this research study and quantify the risks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The next stages are the production of polymers and their preparation to the form compliant with the requirements of buyers. There is also an approach in which only two main steps are taken into account: production of monomers and production of polymers [Alsabri et al 2021].…”
Section: Energy Needs At the Stage Of Production Of Virgin Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…The next stages are the production of polymers and their preparation to the form compliant with the requirements of buyers. There is also an approach in which only two main steps are taken into account: production of monomers and production of polymers [Alsabri et al 2021].…”
Section: Energy Needs At the Stage Of Production Of Virgin Polymersmentioning
confidence: 99%
“…For example, in EU countries, gas prices for industrial customers in the first half of 2019 ranged from 0.02 EUR/kWh (Belgium) to 0.06 EUR/kWh (Finland) (EU average price: 0.03 EUR/kWh) [Natural gas Eurostat 2021]. For comparison, in the USA, the average price of natural gas for industrial customers is 130 USD/1000 Nm 3 (Nm 3 -normal cubic meter) (as of January 2020) [Natural gas, EIA 2022] -approx. 56% lower than the average price in the EU (0.03 EUR/kWh = 297 USD/1000 Nm 3 ; the calorific value of natural gas 33 MJ/Nm 3 and the exchange rate 1.08 USD/EUR were used for conversion).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only is the polymer industry facing a depletion of raw materials, but the production process also has an irreversible negative impact on the environment. For example, studies have shown that the equivalent CO 2 emissions per kilogram of polypropylene and polyethylene produced are 1.34 and 1.48 kg, respectively [ 2 ]. In addition to this, only 14% of plastic packaging is collected for recycling after use and a significant amount escapes into the environment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%